(untitled) (The Journal of Plant Protection Sciences, 2021)
Post application population proliferation (build up) and spread of Trichoderma spp., Trichoderma harzianum and Trichoderma viride in three different types (sterilized, solarised and natural) clay loam soil at 50% water holding capacity (pH 6.5) was studied both under laboratory and field conditions following two types of delivery systems, through organic based (vermicompost + neem cake (90% + 10% w/w)) and seed based (sterilized wheat seed) inocula. The population proliferation and spread of the antagonists were faster when they were applied through organic based inoculums over that of seed based inoculums from the point of application. Similarly population proliferation and spread of the antagonist was more rapid in sterilized soil followed by solarised soil and natural soil respectively. Among the two species of Trichoderma, T. harzianum have spread faster than T. viride.